Pengaruh waktu pengepresan terhadap sifat mekanik komposit kenaf / polypropylene - Sahid Bayu Setiajit; Heru Sukanto; Wijang Wisnu Raharjo (Jurnal Teknik Mesin Indonesia, 2016)
Natural fiber composite is the one of eco friendly composite. Natural fiber such as jute, banana,rosella, rami and kenaf are able tobe a good reinforcement material for thermoset or thermoplast composite. Composit using natural fiber reinforcement can be upgraded by adding more pressing time in the forming process. The aim of this research is to investigate the influence of pressing time adding variation towards mechanical properties of mat composite of kenaf- PP fiber. Mat composite of kenaf- PP fiber is processed by using simple hot press method. The temperature used in the pressing process is 180 0C with 7bar of pressure. The variation of pressing time are 5, 10, 15, 20,25 minutes. Mechanical properties that have been tested are tensile, bending, impact and density. The facture of the composite is observed using scanning electron microscopy (SEM). The 25 minutes pressing time variation resulting the bending and tensile strength of mat composite of kenaf- PP fiber respectively : 39,37 MPa and 25,27 Mpa. The highest impact strength is 20,25 kJ/m2 from 5 minutes of variation of pressing time.